IMPROVEMENT OF THEORETICAL, METHODOLOGICAL AND OBJECTIVE SYSTEM METHODOLOGY IN THE ANALYSIS OF SUSTAINABLE DEVELOPMENT - Kalandarova Nargiza Narimanovna (American Journals, 2024)
There are certain problems that require scientific research in terms of developing a methodology for a set of methods for assessing, analyzing and forecasting the stability of economic activity of economic entities. It is urgent to partially eliminate the shortcomings in the theory and methodological rules of the comprehensive economic analysis of the stability of the development of the economic entity.
Keywords: Stability, financial stability, concept of stability, principles of stability, sustainable development, financial situation, export, import, types of stability, method of analysis.